Differential Expression of miR-31 between Inflammatory Bowel Disease and Microscopic Colitis - Zhang, Chen; Zhao, Zijin; Osman, Hany; Watson, Rao; Nalbantoglu, ILKe; Lin, Jingmei (MicroRNA, 2014)
Background: Idiopathic inflammatory bowel disease (IBD) and microscopic colitis (MC) are distinct entities. However, patients with intermittent episodes of IBD and MC that are encountered in a clinical setting puzzle clinicians and pathologists. This study examined whether microRNA assisted in the classification of IBD and MC. Design: Small RNA was extracted from formalin-fixed, paraffin-embedded (FFPE) colon tissue and qRT-PCR was performed from cohorts of normal control (n=38), ulcerative colitis (n=36), Crohns disease (n=26), collagenous colitis (n=36), lymphocytic colitis (n=30), and patients with intermittent features of IBD and MC (n=6). Results: Differential expression of miR-31 distinguished IBD (ulcerative colitis and Crohns disease) from MC (collagenous colitis and lymphocytic colitis), confirming the specificity of miR-31 expression in IBD (P=0.00001). In addition, expression of miR-31 was increased in collagenous colitis compared to that of lymphocytic colitis (P=0.010). Among 6 patients with alternating episodes of IBD and MC, one patient had matching miR-31 expression in different phases (lymphocytic colitis to ulcerative colitis, and then back to collagenous colitis). The other 5 patients had MC-like expression patterns in both MC and IBD episodes. Conclusion: In summary, IBD and MC have distinct miR-31 expression pattern. Therefore, miR-31 might be used as a biomarker to distinguish between IBD and MC in FFPE colonic tissue. In addition, miR-31 is differentially expressed in colonic tissue between lymphocytic colitis and collagenous colitis, suggesting them of separate disease processes. Finally, patients with alternating IBD and MC episodes represent a diverse group. Among them, the majority demonstrates MC-like miR-31 expression pattern in MC phases, which seems unlikely to support the speculation of MC as an inactive form of IBD. Although the mechanisms deserve further investigation, microRNA is a potentially useful biomarker to differentiate IBD and MC.
Keywords: Collagenous colitis